A Study on the Effects of Shift Work Management on Employee Well-Being in the Manufacturing Sector - Mendrofa, Indah Afridayanti; Palupiningtyas, Dyah (PT. Riset Press International, 2025)
This study explores the impact of shift work management implementation on employee well-being in the manufacturing industry of Semarang Regency. Using a qualitative approach with a phenomenological design, the research involves 28 informants, including shift employees, supervisors, HR practitioners, and labor union representatives. Data was collected through in-depth interviews, participant observation, and focus group discussions. The findings reveal the multidimensional impact of shift work on physical health (80% experienced sleep disturbances), mental health (75% reported increased stress levels), and social well-being (85% faced work-life balance disruptions). Key moderating factors include the shift rotation system (the 3-2-2 model with a 75% satisfaction rate) and individual factors such as age and work experience. Effective adaptation strategies encompass sleep management at the individual level and flexible scheduling at the organizational level. This study contributes to the development of an integrative and context-specific shift work management model while providing practical recommendations to optimize the well-being of shift workers in the manufacturing industry.